EVALUASI KEPUASAN PENGGUNA WI-FI DENGAN METODE IMPORTANCE-PERFORMANCE ANALYSIS DAN CUSTOMER SATISFACTION INDEX (Studi Kasus UGM-Hotspot, Fakultas Teknik, Universitas Gadjah Mada) - , Maulana Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Faculty of Engineering in Gadjah Mada University is one of the faculties that has implemented Wi-Fi technology which follows the policy of single service set identifier named UGM-Hotspot. The implementationâs success of UGMHotspot can be determined by evaluating the Wi-Fi user satisfaction level. User satisfaction is one of the benchmarks that can be accepted as a measurement of successful implementation for information technology (IT) services. This study adopts several previous studies related to the user satisfaction of IT services, especially Wi-Fi. Wi-Fi user satisfaction evaluation model in Faculty of Engineering Gadjah Mada University uses four variables: ease of use, perceived usefulness, quality of service and organizational support. This study was conducted to find out the level of user satisfaction with UGM-Hotspot service and to determine factors that need to be considered (ease of use, perceived usefulness, quality of service and organizational support) in order to increase user satisfaction level. The results of this study show the level of user satisfaction on UGMHotspot service in the Faculty of Engineering Gadjah Mada University is 68.98%. The main priorities for improvements are focused on the quality of services including access speed, connection stability, signal coverage and efficiency of the Internet connection.